Hot rolling of steel - Robert, William L. (Manufacturing engineering and materials processing, 1983)
Number ten of the Manufacturing Engineering and Material Processing series. Includes one page corrigenda laid-in. 800 illustrations clarifying key points. Thorough account of the hot-rolling process and facilities as well as follow-up treatments given to hot-rolled products. Companion volume to "Cold Rolling of Steel" by William Roberts circa 1978 and number two of the series.